Volume 1: Turbomachinery 1996
DOI: 10.1115/96-gt-404
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flow Within Pump Impeller of Torque Converter

Abstract: It is difficult to measure flow patterns within rotating elements of a torque converter due to the complicated construction. Therefore, the numerical calculation is considered to be an effective tool to know the internal flow. Three-dimensional incompressible turbulent flow within a pump impeller of an automotive torque converter was analyzed numerically at three different speed ratios, 0.02, 0.4 and 0.8 under the same inlet boundary condition. The speed ratio was defined as the ratio of rotating speed of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Significant analysis results for flow field characteristics, such as separated and secondary flows, have been reported. (1)(2)(3)(4) With the assistance of more advanced computers, large eddy simulations have been applied to the internal flow in a torque converter, and the results indicated that it is necessary to perform unsteady calculations to understand the internal flow field. (5) However, CFD still has limitations, and must be validated by actual experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Significant analysis results for flow field characteristics, such as separated and secondary flows, have been reported. (1)(2)(3)(4) With the assistance of more advanced computers, large eddy simulations have been applied to the internal flow in a torque converter, and the results indicated that it is necessary to perform unsteady calculations to understand the internal flow field. (5) However, CFD still has limitations, and must be validated by actual experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The pump was shown to be the major source of loss in the speed ratio range where vehicles are most frequently operated in everyday driving. Flows through the pump impeller (10), (11) as well as through the three elements (9), (12) were computed by using CFD codes. Some of the computational results showed good qualitative agreement with the measured flow patterns.…”
Section: Introductionmentioning
confidence: 99%